A ROOT CAUSE ANALYSIS OF PRODUCT DEFECTS IN FOAM BLOCK MANUFACTURING: THE CASE OF CV KARYA JAYA - Sudarno, Natania Alietta; Fernando Mulia (Media Riset Bisnis & Manajemen, 2024)
The manufacturing industry plays a vital role in national economic growth; however, inconsistent product quality can result in financial losses and decreased customer satisfaction. CV Karya Jaya, a foam block manufacturer based in Bandar Lampung, reported an average defect rate of 5.86% from January to August 2024, exceeding its internal standard of 5%. This study aims to identify the root causes of product defects using the cause-and-effect diagram method through a qualitative descriptive approach. Data were collected via direct observation, in-depth interviews, and internal documentation, then analyzed using coding techniques and data triangulation. The findings reveal that four major defect types: porosity, unexpanded foam, color mismatch, and inaccurate cutting, are influenced by machinery, methods, materials, manpower, and environmental factors. These results indicate the need for systemic improvements in operational aspects, including SOP updates, regular staff training, improved machine maintenance, and strengthened quality control oversight. This research offers practical contributions for quality improvement strategies in medium-scale manufacturing firms seeking to reduce losses and enhance product competitiveness.